Sociodemographic Profile and Comorbidities of Children with Epilepsy Attending in Child Development Centre (CDC) of Dhaka Shishu Hospital - Quaderi, Humaira Rafiqa; Sharker, Shaoli; Kanta, Shayla Imam; Mahbub, Mustafa (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Epilepsy is the most common conditions encountered in most paediatric neurology clinics in many parts of the developing world. It is important to understand the sociodemographic profile of children with epilepsy and also to recognize the comorbidities associated with themfor planning management and developing wider services within the country. Objectives: The present study aimed at understanding the socio-demographic profileand comorbidities of children with epilepsy, seeking treatment at a tertiary care hospital in Bangladesh. Methods: This retrospective observational study was conducted in an epilepsy clinic of Paediatric Neuroscience Department of Dhaka Shishu Hospital (DSH) over a period of 3 years from January 2013 to December 2015. During this period 1 year follow up record of each patient was analysed. Information on biodemographic data, clinical and developmental assesment made by a multidysciplinary team was analysed. Results: A total 120 children who had epilepsy were included in this study.The median age at presentation was 2.4 years. Male were 69(58%) and female were 51(42%). Most of the children came from rural area (58%, n=70). Middle income families were over presented (58%). 82% had a history of perinatal asphyxia. Motor, speech impairment and malnutrition were found more who had H/O perinatal asphyxia (P value 0.002,0.005 and 0.03 respectively. Conclusion:In conclusion, epilepsy is one of the commonest neurological morbidity in our environment. This study has provided important information about sociodemographic profile and associated comorbidities in children with epilepsy. This information can be used as a guideline for developing services for children with epilepsy and in prevention of some detectable causes in our countries like birth asphyxia which is found large number in this study. DS (Child) H J 2019; 35(1) : 48-54